2020
DOI: 10.18332/tpc/126631
|View full text |Cite
|
Sign up to set email alerts
|

Assessing factors influencing smoking and smoking cessation within Chinese communities in the Greater Vancouver Area: A qualitative exploratory study

Abstract: INTRODUCTION The prevalence of smoking is high within Chinese-Canadian communities and there is a lack of culturally and linguistically appropriate smoking cessation resources and services. We aimed to ascertain factors affecting smoking and smoking cessation from the perspectives of current smokers and key informants. METHODS As part of a multistage mixed-methods study taking place from January 2013 to June 2014, a qualitative exploratory study design was conducted applying a community-based participatory res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Various factors have been found to affect smoking status, including age, socioeconomic status, level of education, peer smoking, the attitudes of family and friends, lifestyle, stress, self-esteem, and health concerns [13][14][15][16][17]. A survey study among 3658 adults in five countries, including China, Jordan, India, Taiwan, and Saudi Arabia, showed that males, adults older than 25 years, and those working in the medical field were more likely to smoke [16].…”
Section: Introductionmentioning
confidence: 99%
“…Various factors have been found to affect smoking status, including age, socioeconomic status, level of education, peer smoking, the attitudes of family and friends, lifestyle, stress, self-esteem, and health concerns [13][14][15][16][17]. A survey study among 3658 adults in five countries, including China, Jordan, India, Taiwan, and Saudi Arabia, showed that males, adults older than 25 years, and those working in the medical field were more likely to smoke [16].…”
Section: Introductionmentioning
confidence: 99%
“…Third, our findings cannot be generalized because factors associated with quit rate differ across social, cultural, and economic environments. 34 Nevertheless, our study is significant because it focused on smoking cessation in a large number of Asian female smokers while most smoking cessation research literature has focused on non-Asian smokers. Further studies are needed to investigate the connection between female smokers’ mental health and smoking cessation alongside biological verification, and to increase initial counseling sessions for them to promote quit rate.…”
Section: Discussionmentioning
confidence: 99%
“…Communication barriers and style, social aspects of smoking, related beliefs, and values corresponding to Mandarin and Cantonese cultural practices were also considered. More details of the educational materials development can be found in a previous publication 21 . As part of the educational program, participants also completed a triggers and withdrawal symptoms checklist to help monitor their progress throughout the program intervention.…”
Section: Educational Program Materialsmentioning
confidence: 99%